ما بعد ولاية الفقيه؛ النظريات السياسية الشيعية المعاصرة - Muhammad Kholid Muslih (Universitas Darussalam Gontor, 2017)
The development of political thought of contemporary Syiah 12 Imams is not ended by the discourse of “Wilâyat al-Faqîh”; but actually the mullahs always try to explore and give ideas on other concepts which are considered more perfect. Using descriptive-analytical method, this research tries to reveal the dynamics of the study of Syiah political thought through the appearance of various new concepts initiated by the mullahs of the contemporary Syiah 12 Imams since Iranian Revolution and Khumaini’s lifetime till nowadays. The research has concluded that the political thought of Syiah has not been completed yet since the beginning of its appearance. Hence, the concept of “Wilâyat al-Faqîh” is not just a political theory and the last alternative to build an ideal country during “al-Ghaibah al-Kubra”, but it will continue to develop till comes near to the political concept of Ahlusunnah. This indicates that the political concept of Ahlusunnah is a well-set concept and theory of politics because it has been proven well-tested conceptually and in application, and it is also almost similar to the originality of Islamic thought and the prophetic guidance, and it is very appropriate to be applied in the future. The new ideas of the mullahs will have an important role to get Syiah closer to Ahlusunnah in the political concept after being torn apart by enmity as the consequence of the extreme thought of mysticism which infiltrates Syiah thought.